Torsed gangrenous Meckel’s diverticulum resulting in acute small bowel obstruction: a case report - Shrivastava, Vaibhav; Kumar, Arun; Sabberwal, Archit; Katiyar, Radhika; Verma, Akhilesh (International Surgery Journal, 2025)
<!–StartFragment–> Meckel’s diverticulum is the most frequent congenital anomaly of the gastrointestinal tract, with a prevalence of about 2%. Although often asymptomatic, it may lead to complications such as bleeding, obstruction, or inflammation. Torsion of the diverticulum is exceptionally rare and may present with features of acute intestinal obstruction. We describe the case of a young male who presented with signs of small bowel obstruction. Exploratory laparotomy revealed a twisted, gangrenous Meckel’s diverticulum causing acute obstruction of the ileum. Resection of the affected ileal segment with double barrel ileostomy was performed, ileostomy closure done after 3 months and the patient made an uneventful recovery. Although rare, torsion of Meckel’s diverticulum should be considered as a possible cause of intestinal obstruction. Timely recognition and surgical intervention are crucial for a favourable outcome. <!–EndFragment–>